Presence of leucocytes in prostatic secretions correlates with the severity of lower urinary tract symptoms. (30th April 2020) - Lee, Min Ho; Lee, Chunwoo; Choi, Jae Hwi; Jeh, Seong Uk; Lee, Sin Woo; Choi, See Min; Hwa, Jeong Seok; Hyun, Jae Seog; Chung, Ky Hyun; Kam, Sung Chul
Abstract: We investigated the correlation between the presence of leucocytes in expressed prostatic secretion and the lower urinary tract symptom severity by retrospectively reviewing 699 men with lower urinary tract symptoms. The patients were evaluated by the International Prostate Symptoms Score and the Overactive Bladder Symptoms Score and underwent expressed prostatic secretion testing. Patients were classified into groups 1 and 2 based on the expressed prostatic secretion leucocyte count. The mean total and storage score of the International Prostate Symptoms Score, and mean total Overactive Bladder Symptoms Score were higher in group 1. Urine flow metrics showed that voided volume and maximum flow rate were lower in group 1. The scores for International Prostate Symptoms Score questions 4, 6 and 7 and Overactive Bladder Symptoms Score question 2 were higher in group 1 and showed a weak positive correlation with expressed prostatic secretion. Voided volume and maximum flow rate showed the strongest correlation, although International Prostate Symptoms Score question 7 and Overactive Bladder Symptoms Score question 2 were the only independent predictors of expressed prostatic secretion. Therefore, leucocytes in expressed prostatic secretion are associated with the lower urinary tract symptom severity, particularly nocturnal urination symptoms.